Avaliação de NO2 na atmosfera de ambientes externos e internos na cidade de Araraquara, São Paulo - Ugucione, Cássia [UNESP]; Machado, Cristine de Mello Dias [UNESP]; Cardoso, Arnaldo Alves [UNESP] (Sociedade Brasileira de Química, 2009)
The seasonal behavior of NO2 concentration shows a maximum occurring during sugarcane crop and this suggests that the biomass burning is significant source of emission at this time of the year. Along the day, the variation of the NO2 showed a decrease during the increased sunlight and an increase thereafter, caused by occurrence of photochemical reactions. Measurements of NO2 were done inside of residential and industrial kitchens and also inside of a parking garage located in the underground of a supermarket building. The indoor concentrations of NO2 were significantly higher than the concentrations of the external atmosphere and it shows the importance of the sources of internal emissions.
Evaluation of NO2 in the outdoor and indoor atmospheres at Araraquara, São Paulo
Keywords: nitrogen dioxide concentration; nitrogen dioxide indoor; nitrogen dioxide outdoor